Membongkar Kejahatan Cukai: Pendekatan Kriminologis terhadap Praktik dan Penegakan Hukum - Zurfian Adi Asma; Moch Alfatah Alti Putra; Iswandy Rani Saputra; Aburizal Fatwa Ramli; Armin Hasti (Jurnal Litigasi Amsir, 2025)
This study examines excise crime in Indonesia’s trade context by focusing on the circulation of illegal cigarettes without authorization in the jurisdiction of the Customs and Excise Supervision and Service Office Type Madya Pabean C Parepare. It aims to analyze the causes of illegal cigarette circulation and the forms of law enforcement carried out by the customs authority, using a combination of normative and empirical legal research with statutory and case approaches based on regulatory, literature, and field data. The results show that economic constraints, low legal awareness, broad supervisory areas with limited resources, high market demand for cheap cigarettes, and sanctions that lack a deterrent effect are the main driving factors, while law enforcement is implemented through reporting or in flagrante findings, investigation and sanctioning by Civil Servant Investigators, case file preparation, and submission to the Public Prosecutor under applicable criminal procedure and excise regulations